La revolución de la independencia del Perú (1860) de Benjamín Vicuña Mackenna en la historiografía peruana - Peralta Ruiz, Víctor (2013)
This article will center on the impact of the work La revolución de la independencia del Perú (Lima, 1860) by the Chilean historian Benjamín Vicuña Mackenna (Santiago, 1831-1886). It will discuss the novelty of the use of the term «revolution» in an age in which Peruvian historiography rejected the political use of that term. It will then discuss the reception of Vicuña’s work in Peruvian historiography in the nineteenth and twentieth centuries. In particular, it underlines the reasons why this work was not included as a supporting text in the formation of the nationalist discourse of the Peruvian state.